Local History and Development of National Awareness in the Perspective of Multicultural Education; Historical Study of Dugderan Tradition in Semarang City - Khoirul Anwar; Djono Djono (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
The aim of this article is to understand Dugderan in Semarang City on the educational multicultural perspective related to national awareness development based on local tradition history. Dugderan is a routine ritual collaborative between community and Semarang City Government which was held approaching month of Ramadan. Ramadan is the rated month holy by Muslims throughout the world is not except for Semarang City community. Tradition Dugderarn has in progress since hundred years ago and still​ in progress until now. Dugderan is another term for the cultural festival in which it is held covering complexity life social community which includes religious, tolerance diversity and economy. Research This implemented with method qualitative with approach ethno-videography. The data collection process includes audio visual production through observation in a way live and interview to related informants​ with tradition Dugderan. In addition, researchers use method studies library to enrich data besides from source field. In religious, Dugderan become marker will the implementation of fasting in the month of Ramadan by the people of Semarang City. Tradition Dugderan is representation tolerance diversity Semarang City community consisting of on multi-entity. On the aspect economy, tradition Dugderan become a magnet for public for buyers and traders are the majority consists of on group intermediate to below. With thus Dugderan become a people's festival that can unite all middle group​ diversity national. Semarang City is miniature diversity that becomes central civilization local that has intertwined since the time of Ancient Mataram. As center diversity, Semarang City can become example practice good on the scene national both locally and globally in build awareness nationality in any era.